ClinGen's GenomeConnect registry enables patient‐centered data sharing. Issue 11 (11th October 2018) - Savatt, Juliann M.; Azzariti, Danielle R.; Faucett, W. Andrew; Harrison, Steven; Hart, Jennifer; Kattman, Brandi; Landrum, Melissa J.; Ledbetter, David H.; Miller, Vanessa Rangel; Palen, Emily; Rehm, Heidi L.; Rhode, Jud; et al.
Abstract: GenomeConnect, the NIH‐funded Clinical Genome Resource (ClinGen) patient registry, engages patients in data sharing to support the goal of creating a genomic knowledge base to inform clinical care and research. Participant self‐reported health information and genomic variants from genetic testing reports are curated and shared with public databases, such as ClinVar. There are four primary benefits of GenomeConnect: (1) sharing novel genomic data—47.9% of variants were new to ClinVar, highlighting patients as a genomic data source; (2) contributing additional phenotypic information—of the 52.1% of variants already in ClinVar, GenomeConnect provided enhanced case‐level data; (3) providing a way for patients to receive variant classification updates if the reporting laboratory submits to ClinVar—97.3% of responding participants opted to receive such information and 13 updates have been identified; and (4) supporting connections with others, including other participants, clinicians, and researchers to enable the exchange of information and support—60.4% of participants have opted to partake in participant matching. Moving forward, ClinGen plans to increase patient‐centric data sharing by partnering with other existing patient groups. By engaging patients, more information is contributed to the public knowledge base, benefiting both patients and the genomics community. Abstract : The GenomeConnect patient registry engages patients in data sharing of genomic and phenotypic data. This data sharing allows for the dissemination of novel genomic data, sharing of case‐level information, provision of a method to receive variant interpretation updates, and connection of participants with one another and with other stakeholders. By engaging patients, more information is contributed to the public knowledge base benefiting both patients and the genomics community.